Antiviral clerodane diterpenoids from Dodonaea viscosa. Issue 49 (8th December 2016) - Zhang, Lai-Bin; Liao, Hai-Bing; Zhu, Hai-Yan; Yu, Mei-Hua; Lei, Chun; Hou, Ai-Jun
Abstract: Seven new clerodane diterpenoids, dodovisnoids A−G (1 –7 ), were isolated from Dodonaea viscosa . The structures of these compounds were identified by extensive spectroscopic data. The absolute configurations of1, 2, and6 were assigned by X-ray crystallographic analysis. Compound1 is an unprecedented clerodane diterpenoid possessing a new carbon skeleton that could biogenetically derive from 5, 10-secoclerodane. Compounds2 –5 are rare cyclopropyl-modified clerodanes and6 is the first dinor-clerodane featuring an alkynyl moiety. Compounds4 –7 showed antiviral activity against herpes simplex virus type 1 (HSV-1) in vitro. Graphical abstract: